Enhancing the Uptake of Learning Through Simulation in Health : Final Report. - Rudd, Cobie (Office for Learning and Teaching, 2013)
Final report of a Teaching Fellowship at Edith Cowan University. This fellowship developed and introduced a new conceptual framework, the Simulation Valid Elements (SVE) model, that profiles emotional validity, environmental validity and situational validity as critical elements germane to the training in human factors through simulation. Through addressing suboptimal communication patterns, improving situational awareness, and building emotional and social intelligence within the current and future health workforce, the aim is to have a positive impact on patient safety.